25 Hz Magnetic Seizure Therapy Is Feasible but Not Optimal for Chinese Patients With Schizophrenia: A Case Series - Jiang, Jiangling; Li, Qingwei; Sheng, Jianhua; Yang, Fuzhong; Cao, Xinyi; Zhang, Tianhong; Jia, Yuping; Wang, Jijun; Li, Chunbo (Frontiers in Psychiatry, 2018)
Magnetic seizure therapy (MST) is a potential alternative to electroconvulsive therapy (ECT), but there is currently a lack of reports about MST in Chinese patients with schizophrenia. Our objective was to investigate the feasibility and acceptability of add-on MST in the treatment of patients with schizophrenia. Eight patients with schizophrenia were enrolled in a case series study to receive ten sessions of add-on MST over four weeks. The MST was administrated using 25 Hz at 100% output with a titration duration ranging from 4 s to 20 s by 4 s. The Positive and Negative Syndrome Scale (PANSS) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) were employed to measure the symptom improvements and the cognitive effects, respectively. Six patients completed at least one-half of the planned sessions. Five showed a reduction in PANSS total score, and three achieved clinical response (≥ 30% reduction). Three of the participants receiving the RBANS, showed either improvements or no changes in the memory function. Regarding the subjective complaints about MST, two reported dizziness, and only one reported memory loss. Approximately one-fourth of the treatment sessions produced only brief seizures (less than 15s). Overall, employing MST to treat Chinese patients with schizophrenia appeared feasible and acceptable. However, further evidence is needed to determine the therapeutic efficacy and effects of MST on the cognitive functions of patients with schizophrenia.